Komunikasi Interpersonal Keluarga Tentang Pendidikan Seks Pada Anak Usia 1-5 Tahun - Amina Erni (Jurnal Dakwah dan Komunikasi, 2017)
Childhood is the age before entering formal education institution of Elementary School (SD). Children enter primary school after the age of six, the beginning of the school age phase. During the childhood phases the physical development of children, male or female, increases rapidly. The muscles, nerves, and skeletons of their bodies lead to maturity. Moving skills accelerate, ranging from large muscle movements, muscle shrinkage, and the cooperation of eye movements and hand movements. Children are in transition between the vital period and the intellectual period. The childhood phase is a critical period in the development of the personality of children. According to the psychoanalytic theory of Sigmund Freud in the childhood phase is within the level of psychosexual development and begin to attract and gain pleasure from genital stimulation. They begin to realize and fascinated by the differences between men and women. Attitudes and the way parents educate their children are very influential on the child's personality. Proper sex education will be a provision for children to face the world around. Difase this new child will know the outside world. If the child has not been equipped with intellectuals about sex education, then the child will experience confusion with the things he will meet. The child will only respond and show the stimuli from the environment he is, only based on what he experienced and he felt. Sometimes children are removed from the supervision of their parents. Family role is needed. Because the family is the child's first social environment, it is expected to implement sex education. Can be applied in the family environment through interpersonal communication between parents and their children.